Physical activity and psychological distress: social gradients of living in poverty - Swank, Aaron C. (Kansas State University, 2017)
INTRODUCTION: Research has focused on the relationship between socioeconomic status and physical activity, yet there are limited examinations which directly address social groups dealing with major issues associated with insufficient income. Studies have neglected the role of psychosocial stressors, such as financial stress, food insecurity, availability of government assistance programs, as well as psychological distress relative to the relationship between physical activity and low-income status. The purposes of this study were threefold: 1) to describe the multidimensional characteristics of life among low-income populations; 2) to examine how psychosocial stressors and health conditions vary across subsets of low-income groups; and 3) to examine the relationship among income, psychological distress and physical activity within low-income populations. METHODS: Data from the 2015 National Health Interview Survey (NHIS) were analyzed for the purposes of this investigation. Descriptive statistics were calculated for the low-income status individuals who provide complete data for all variables of interest to this study. A series of chi-square analyses were conducted to determine whether key psychosocial stressors, health behaviors, and health conditions differed by low-income (FIPR) groups. Two stepwise logistic regression analyses were conducted to examine these factors and their relationships with moderate-intensity (MPA) and vigorous (VPA)-intensity physical activity. RESULTS: Overall, women made up 58.5% of the sample size. Blacks/African Americans accounted for 20.6% of the sample, yet 28.0% of FIPR Group 1 identified as Black/African American. FIPR Group 1 was disproportionately unemployed, with 63.5% unemployed compared to 46.9% for the sample. One-quarter (25.9%) of the entire sample reported severe psychological distress, yet 33.9% of FIPR Group 1 and 30.8% of FIPR Group 2 reported severe distress. Nearly three-quarters (70%) of the sample was overweight or obese and 44.2% lived with at least one chronic disease at the time the survey was taken. Overall, 67.9% of the sample reported zero minutes of VPA and 51.3% reported zero minutes of MPA. Both psychological distress and income showed significant relationships with VPA. Psychological distress remained significantly associated with VPA after controlling for all covariates; however, income was no longer related to VPA after demographic and health-related variables were added to the model. Income was not related to MPA. Psychological distress demonstrated a weak relationship with MPA before the other covariates were added to the model, at which point the relationship became non-significant. Only the relationship between psychological distress and VPA was significant in the final models. Although some of the psychosocial stressor, demographic, and health-related variables contributed to the relationships between income, physical activity, and psychological distress, these variables explained only a small portion of the variance in both MPA and VPA. CONCLUSION: Low-income individuals are faced with difficult decisions and are limited in the choices they can make to improve health. It is important to understand the multidimensional characteristics of life under limited income to better serve and improve the health of low-income populations. Further study of the relationships among income, physical activity and psychological distress is needed to further this understanding.
Keywords: Physical activity; Psychological distress; Psychosocial stress; Income